(untitled) (Web of Teachers: Inderscience Research, 2026)
The reforms being implemented in the field of education in our republic necessitate the full informatization of the education system, the revision of traditional teaching content, the integration of academic disciplines, and the organization of instruction based on the effective use of modern pedagogical technologies. In turn, this creates the need to establish a unified information and educational environment within educational institutions, to develop and effectively utilize information databases, and to improve educational and regulatory documents on the basis of interdisciplinary integration.